(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In the article orographical and structural forms of Central Armenia as well as their ratio are considered. The profiles of the relief were made by Geographical Information Systems on the basis of electronic topographic maps of scale 1:200 000. The received data can be usefull for the prediction of a place of occurrence of earthquakes, seismic zoning, and electronic maps - for analysis and modeling of sliding processes.